Hwa-byung (anger syndrome) as a risk factor for suicidal ideation in MZ generation: a survey study in South Korea - Kwon, Chan-Young (Frontiers in Psychology, 2024)
Introduction: Suicide is a critical global public health issue, with South Korea exhibiting the highest suicide rate among OECD countries at 24.1 per 100,000 people in 2020. This study focuses on suicidal ideation (SI) within South Korea's Millennials and Generation Z (Generation MZ) by examining the impact of anger and hwa-byung (HB), a culture-bound anger syndrome.The online survey was conducted between June 7 and 12, 2024. The inclusion criteria for this study were the following: (1) generation MZ (i.e., those born between 1980 and 2005); (2) those without a history of mood disorders (i.e., depressive disorders or bipolar disorder); (3) those of Korean nationality and residing in South Korea. Demographic variables and clinical variables including SI, HB, and depression were investigated. The chi-square test or t-test was used to compare the differences between the SI and non-SI groups. Additionally, binary logistic regression analysis was performed to analyze factors associated with the presence of SI. Finally, Pearson's correlation coefficients were calculated to explore HB symptoms that were highly associated with SI.Results: Total 457 participants were included. The survey revealed an overall prevalence of SI of 38.07%, with 18.82% reporting "much" or more SI and 4.81% reporting "very much" SI. Significant differences were found between the SI and non-SI groups in HB symptoms, depression, anxiety, perceived stress, trait anger, state anger, anger-in, and anger-out (all p<0.001). Logistic regression analysis identified HB symptoms (odds ratio [OR], 1.05; 95% CI, 1.00-1.11; p=0.050), depression (OR, 1.41; 95% CI, 1.23-1.62; p<0.001), and state anger (OR, 1.14; 95% CI, 1.05-1.24; p=0.002) as significant factors for SI. The mediating factors confirmed the direct and indirect effects of HB symptoms on the presence of SI. Pearson's correlation coefficients between HB symptoms and SI severity ranged from 0.241 to 0.536, with physical symptoms, such as heat sensation and chest pressure, showing high correlations (0.426 to 0.476).These findings highlight the need for mental health policies that integrate Korean medical approaches into suicide prevention. Future research should confirm these results using larger, nationally representative samples to improve generalizability and further explore HB and suicidality in diverse populations.